Investigation of the Co‐Dependence of Morphology and Fluorescence Lifetime in a Metal‐Organic Framework. Issue 27 (12th May 2016) - Schrimpf, Waldemar; Ossato, Giulia; Hirschle, Patrick; Wuttke, Stefan; Lamb, Don C.
Abstract : Porous materials, due to their large surface‐to‐volume ratio, are important for a broad range of applications and are the subject of intense research. Most studies investigate the bulk properties of these materials, which are not sensitive to the effect of heterogeneities within the sample. Herein, a new strategy based on correlative fluorescence lifetime imaging and scanning electron microscopy is presented that allows the detection and localization of those heterogeneities, and connects them to morphological and structural features of the material. By applying this method to a dye‐modified metal‐organic framework (MOF), two independent fluorescence quenching mechanisms in the MOF scaffold are identified and quantified. The first mechanism is based on quenching via amino groups, while the second mechanism is influenced by morphology. Furthermore, a similar correlation between the inherent luminescence lifetime and the morphology of the unmodified MOF structure is demonstrated. Abstract : A novel approach to elucidate the structural, functional, and morphological properties of (in)organic materials using correlative fluorescence lifetime image microscopy and scanning electron microscopy is presented. Using this method, a correlation between the morphology and the fluorescence lifetime in a metal‐organic framework (MOF) is shown. Additionally, two quenching mechanisms of fluorescein in this MOF are identified and quantified.